The Comoedia Togata, a ‘Roman’ Literary Genre? - Rallo, Guiseppe Eugenio (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper aims to shed fresh light on the Togata. By analysing the extant fragments, I will investigate if and in what sense it may be defined as a ‘Roman’ literary genre. I will focus on its ‘Roman-ness’, and I will highlight that it is a complex concept, without the ‘nationalistic’ connotations that one normally gives to the notion. I will demonstrate that the Togata is ‘Roman’ because it betrayed an attempt at creating a genre distinguished from the Palliata, and it had a widespread ‘Roman’ patina, with settings, names, and stereotypes which one would not find in other contemporary genres, in particular the Palliata. At the same time, I will also reflect on the fact that the Togata was a multifarious genre, with Latin, Italic, and Greek elements, and I will show that this was, paradoxically, another aspect of its ‘Roman-ness’.